Single electron ionization of multishell atoms: dynamic screening and post-prior discrepancies in the CDW-EIS model - Monti, Juan Manuel (2013)
A complete formulation of the post-version of the continuum distorted wave-eikonal initial state (CDW-EIS) model is used to investigate single ionization of multishell atoms by fast bare proton beams. The influence of the non-ionized electrons on the dynamic evolution is studied for each of the different shells of the targets. Its inclusion was made by means of the parametric Green–Sellin–Zachor potential. In this way, it is shown that discrepancies between the prior- and post-versions of the CDW-EIS model are avoided for any nl states of the systems studied here. The present analysis is supported by comparisons with existing experimental electron emission spectra